2020
DOI: 10.1007/s00018-020-03465-3
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide targets EGFL6 to inhibit EGFL6/PAX6 axis-driven angiogenesis in small bowel vascular malformation

Abstract: Background Small bowel vascular malformation disease (SBVM) is the most common cause of obscure gastrointestinal bleeding (OGIB). Several studies suggested that EGFL6 was able to promote the growth of tumor endothelial cells by forming tumor vessels. To date, it remains unclear how EGFL6 promotes pathological angiogenesis in SBVM and whether EGFL6 is a target of thalidomide. Methods We took advantage of SBVM plasma and tissue samples and compared the expression of EGFL6 between SBVM patients and healthy people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…One factor that has recently captured researchers' attention for its role in angiogenesis is epidermal growth factor-like domain-containing protein 6 (EGFL6) [23]. EGFL6 is a member of the EGF superfamily of proteins; it is also upregulated in tumorigenesis and epithelial-tomesenchymal transition [24][25][26][27]. Xu et al found that osteoblast-like cells secrete EGFL6 in a paracrine manner, triggering EC migration and angiogenesis through activation of the ERK pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…One factor that has recently captured researchers' attention for its role in angiogenesis is epidermal growth factor-like domain-containing protein 6 (EGFL6) [23]. EGFL6 is a member of the EGF superfamily of proteins; it is also upregulated in tumorigenesis and epithelial-tomesenchymal transition [24][25][26][27]. Xu et al found that osteoblast-like cells secrete EGFL6 in a paracrine manner, triggering EC migration and angiogenesis through activation of the ERK pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…Strand-specific libraries were constructed using the TruSeq RNA sample preparation kit (Illumina, San Diego, CA, USA), and sequencing was carried out using the Illumina HiSeq X Ten instrument by the commercial service organization Energy Biotechnology Co., Ltd. (Shanghai, China). As described in a previous study [10,11], the expression of the transcripts was calculated by the FPKM method using Perl. Differentially expressed transcripts (DETs) were determined using the MA-plot-based method with Random Sampling (MARS) model in the DEGseq package between different time points.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Protein Agarose Beads (50 μL) and anti-FOXP2 antibody (4 μg) were added to the sonicated cell supernatant to immunoprecipitate the chromatin. Finally, the immunoprecipitated DNA was amplified as described in the literature [11]. The sequence for the caspase-1 promoter is listed in supplementary material 1.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor that has captured recent attention for its role in angiogenesis is epidermal growth factor-like domain-containing protein 6 (EGFL6) [23]. EGFL6 is a member of the EGF superfamily of proteins; it is also upregulated in tumorigenesis and epithelial-to-mesenchymal transition [24][25][26][27]. Xu et al found that osteoblast-like cells secrete EGFL6 in a paracrine manner, triggering EC migration and angiogenesis through activation of the ERK pathway [28].…”
mentioning
confidence: 99%